2014
DOI: 10.1186/bcr3668
|View full text |Cite
|
Sign up to set email alerts
|

An integrated genomic approach identifies persistent tumor suppressive effects of transforming growth factor-β in human breast cancer

Abstract: IntroductionTransforming growth factor-βs (TGF-βs) play a dual role in breast cancer, with context-dependent tumor-suppressive or pro-oncogenic effects. TGF-β antagonists are showing promise in early-phase clinical oncology trials to neutralize the pro-oncogenic effects. However, there is currently no way to determine whether the tumor-suppressive effects of TGF-β are still active in human breast tumors at the time of surgery and treatment, a situation that could lead to adverse therapeutic responses.MethodsUs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…The results of a gene network analysis suggest that some of the phenotypic characteristics may be related to the production by IBD tumors of potent immune suppressant factors, such as TGFβ, that may alter the functional status of the immune response in the tumor microenvironment, though this hypothesis remains to be confirmed. Recent new evidence suggests that in some breast tumors, TGFβ signaling (in association with Smad3) contributes to the maintenance of an anti-proliferative effect manifesting as a reduced tumor proliferative capacity (44). Thus, the potential duality of TGFβ function, as an intrinsic tumor suppressor and potent immunosuppressive cytokine could explain, in part, the low-proliferative phenotype of IBD tumors in general, and an impaired immune response associated with IBD-FID, specifically.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a gene network analysis suggest that some of the phenotypic characteristics may be related to the production by IBD tumors of potent immune suppressant factors, such as TGFβ, that may alter the functional status of the immune response in the tumor microenvironment, though this hypothesis remains to be confirmed. Recent new evidence suggests that in some breast tumors, TGFβ signaling (in association with Smad3) contributes to the maintenance of an anti-proliferative effect manifesting as a reduced tumor proliferative capacity (44). Thus, the potential duality of TGFβ function, as an intrinsic tumor suppressor and potent immunosuppressive cytokine could explain, in part, the low-proliferative phenotype of IBD tumors in general, and an impaired immune response associated with IBD-FID, specifically.…”
Section: Discussionmentioning
confidence: 99%
“… 291 In ER + breast cancers, differing TGFβ/SMAD3-driven gene expression signatures are generated that are able to uncouple the tumor suppressive effects of TGFβ in patient cohorts with good clinical outcomes from the tumor-promoting activities of TGFβ with poorer outcomes. 292 In the near future, greater knowledge about specific gene signatures from individual tumors will be informative for the choice of therapy, such as employing TGFβ antagonists or not. The epigenetic landscape will play an increasingly important role in determining TGFβ-induced phenotypes within specific cell contexts and cancer subtypes.…”
Section: Transforming Growth Factor Betamentioning
confidence: 99%
“…Thus, the mouse model data suggests that, contrary to dogma, tumor-suppressive responses to TGFb may be retained and dominant in some instances of advanced metastatic breast cancer. We previously showed that high expression of a gene signature specifically reflecting tumor-suppressive effects of TGFb was associated with improved metastasis-free survival in clinical breast cancer cohorts (31), which supports the possibility that retention of TGFb tumor-suppressive responses may also be a feature of the human disease. In the context of ongoing clinical trials with TGFb pathway antagonists, our data suggest that good predictive biomarkers will be critical for safe and effective use of these agents, not just to identify patients who will respond therapeutically, but more importantly to eliminate those patients who are at risk for adverse on-target responses.…”
Section: Discussionmentioning
confidence: 61%
“…3C). In contrast, we previously generated a signature [TGFb/SMAD3 tumor suppressor signature score (TSTSS)] that specifically reflects just the tumor cell-autonomous suppressive effects of TGFb, and associates with good outcome in human breast cancer datasets (31). Here, we found that tumors from the StimMet response class show significantly higher expression of the TSTSS signature ( Fig.…”
Section: Tumor Transcriptomics Identify Gene Signatures Associated Wimentioning
confidence: 83%